Aelred of Rievaulx, The Historical Works, trans, by J.P. Freeland, introduction and annotations by M.L. Dutton, Kalamazoo 2005, Cistercian Publications 56, ss. 306 - Groń, Ryszard (Vox Patrum, 2005)
review